DETERMINAN CAPAIAN KONTRASEPSI PADA MASA PANDEMI COVID-19 DI DESA GEDUNG AGUNG KECAMATAN MERAPI - INKA PUTRI; NINA DAMAYATI; Monanisa monanisa (Universitas Negeri Padang, 2022)
The outbreak of the corona virus disease (Covid-19) was first reported in China, precisely in Wuhan. The government provides a solution by doing large-scale social restrictions which result in restrictions on the number of visits and access to health facilities and makes sexual activities of fertile age couples (PUS) increase because they have more time with each other at home. The purpose of this study was to look at the Social, Economic, and Demographic Conditions of Couples of Childbearing Age during the Covid-19 Pandemic and to find out whether the Covid-19 pandemic affected contraceptive outcomes. The research method used is descriptive quantitative. The population of this study were all couples of childbearing age in Gedung Agung Village, East Merapi District, namely 580 PUS. The samples in this study were 25 couples of childbearing age and 1 PKB informant in the eastern Merapi sub-district. Sampling using purposive sampling technique. Data collection techniques using Questionnaires, Interviews and Documentation. Data analysis using Multiple Linear Regression. The results of the study are (1) Social, Economic and Demographic conditions of PUS with high school education as much as 52%, household work 72%, income 2.500.000 – 3.500.000 52%, classified as multipara 60%, the average contraceptive method used is the contraceptive method. periodic injections (2) Based on the T Test, the factors that affect the achievement of contraception in Gedung Agung Village, East Merapi District, are variables in the number of children and work variables. 44.8% while 55.2% was influenced by other variables.